1997
DOI: 10.1088/0029-5515/37/12/i03
|View full text |Cite
|
Sign up to set email alerts
|

Nature of high-Z impurity accumulation in tokamaks

Abstract: The recent experiments on accumulative behaviour of heavy impurities in TEXTOR with test limiters of molybdenum and tungsten and puffing of xenon are briefly reviewed. The results of the reconstruction of the transport coefficients of high-Z ions in the accumulation stage are presented. They confirm the neoclassical nature of the convective particle transport, leading to peaking of the impurity density. A mechanism triggering accumulation, invoking the temperature dependence of neoclassical flows of impurities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
56
0
5

Year Published

2002
2002
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(62 citation statements)
references
References 21 publications
1
56
0
5
Order By: Relevance
“…The temperature gradient term is responsible for the temperature screening effect: the thermal force acts on the impurities in the direction of the thermal gradient and prevents them from penetration into the plasma core. The temperature screening effect has been observed in several tokamak experiments [39,43]. An interesting consequence of this effect is that in a stationary transport regime, its failure can result in an impurity accumulation instability.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…The temperature gradient term is responsible for the temperature screening effect: the thermal force acts on the impurities in the direction of the thermal gradient and prevents them from penetration into the plasma core. The temperature screening effect has been observed in several tokamak experiments [39,43]. An interesting consequence of this effect is that in a stationary transport regime, its failure can result in an impurity accumulation instability.…”
Section: Discussionmentioning
confidence: 89%
“…The enhanced core power loss due to increased impurity radiation leads to further ion temperature decrease and further temperature screening effect failure. The instability threshold is defined in terms of the critical electron density n e (0): n I (0)/n e (0) ∼ 4 × 10 −2 × (D ⊥ /D PS neo ) 2 [43]. Observations in CDX-U plasmas prior to 1999 appeared to satisfy the criteria of the accumulation instability for low-Z impurities [46].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, impurity seeding of both divertor and core plasma is needed to mitigate the heat loads on the divertor [68]. However, radiation levels are limited by: dilution of the fuel in the core; impurity accumulation [69] and impurity sputtering of the tungsten target [70]. In particular, transient heat loads caused by instabilities, decrease significantly the operation domain of plasma facing components, due to thermal stresses and consequent enhanced erosion [71].…”
Section: 232mentioning
confidence: 99%
“…At JET, it has been found that the maximum achievable radiative power fraction in stationary type-I ELMy H-modes is f rad = 0.65. At higher radiative power fractions, the local core radiation power density exceeds the local heating power density and an accumulation instability on the basis of the neoclassical theory develops [21]. This has detrimental effects on the confinement [22], although central heating by ion cyclotron resonance heating (ICRH) might enable high impurity concentrations without accumulation in the plasma core [22].…”
Section: Iter Implicationsmentioning
confidence: 99%